READINESS FOR INTERPROFESSIONAL EDUCATION: PERSPECTIVE FROM MEDICAL AND NURSING STUDENTS - Vivien Puspitasari; Ni Gusti Ayu Eka; Marisa Junianti Manik; Mona Marlina; Neneng Suryadinata; Grace Solely Houghty (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Interprofessional education (IPE) is argued as an educational strategy for promoting communication and collaboration amongst prospective healthcare professionals. The benefits of IPE have culminated in improved patient care leading to enhanced satisfaction for patients and healthcare practitioners. Therefore, further exploration is needed to assess the readiness for IPE through healthcare students’ perspectives, specifically medical and nursing students.This study aimed to assess medical and nursing students’ readiness for IPE and the effect of gender on their readiness.Methods: A quantitative study design using the Readiness for Interprofessional Learning Scale (RIPLS) was employed on 150 medical students and 150 nursing students. Data was analyzed using descriptive and Mann-Whitney statistical analyses.Results: The readiness of IPE score was statistically significantly different between medical and nursing students (p-value <0.0001), with nursing students (Median 4.34) found to have higher readiness or indicate more positive attitudes toward IPE compared to medical students (Median 3.73). Students are found to have a positive attitude or readiness towards IPE. This study also revealed that there was no significant difference in IPE readiness based on genders (p-value 0.087).Conclusion: It is essential to engage students in preparing the implementation of IPE for health sciences courses. Further workshops for IPE can be a strategic step to enhance readiness of the students.